The Development of Video Learning Media Assisted by Canva on the Earth Changes Material for 5th Grade Students of SDN 01 Kuala Gasib - Khasanah, Margfirotul; Fitriyeni, Fitriyeni (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The lack of variation in learning media used in teaching activities has resulted in less-than-optimal learning effectiveness. One of the causes is the limited variety of learning media. This study aims to produce valid and practical video learning media assisted by Canva on the topic of Earth Changes for 5th-grade students at SDN 01 Kuala Gasib. This research is a type of Research and Development (R&D) with the ADDIE model. The subjects of this study were content experts, media experts, language experts, teachers, and 10 students from class VA of SDN 01 Kuala Gasib. The data collection techniques and instruments included interview guidelines and validation questionnaires from content experts, media experts, language experts, as well as practicality questionnaires from teachers and students. Data analysis was conducted qualitatively based on suggestions and comments, and quantitatively based on validation scores and responses. Based on the research results, the final outcome was concluded to be 95.91%, categorized as highly valid. The design expert evaluation obtained a percentage of 97.7%, categorized as highly valid. The language expert evaluation achieved an average percentage of 93.8%, categorized as highly valid. The content expert evaluation achieved an average percentage of 96.3%, categorized as highly valid. Additionally, the teacher response questionnaire yielded 94.50%, while the student response questionnaire scored 94.00%. Therefore, the Canva-assisted video learning media is considered feasible for use in teaching and learning activities.